Hepatocellular Carcinoma: Aetiology and Mechanisms of Development. A Literature Review - K. V. Menshikov; A. V. Sultanbaev; Sh. I. Musin; I. R. Rakhmatullina; I. A. Menshikova; R. R. Abdeev; N. I. Sultanbaeva; E. V. Popova; G. A. Serebrennikov (Креативная хирургия и онкология, 2022)
Liver cancer remains a global challenge of healthcare, with the incidence growing worldwide. According to various authors, over 1 million patients will be diagnosed with liver cancer each year by 2025. The molecular pathogenesis of HCC varies with respect to genotoxic lesions and aetiologies. Although our understanding of the HCC pathophysiology and drivers tends to improve, it is still distant from translation into clinical practice. About 25 % of HCC cases are associated with variant mutations. HCC pathophysiology is a complex multi-step process. The interaction of various factors underlies the early stages of malignant hepatocyte transformation towards the development of HCC. Overall, about 20–25 % of HCC patients have at least one potential driver mutation. Obesity should also be noted as being associated with a higher risk of HCC and various other cancers. Despite many issues in the HCC pathogenesis being already known, the unresolved questions remain. Modern molecular genetic diagnostics and animal modelling of malignant tumours are expanding our horizons of knowledge in this field.